#### Answer

$-6$

#### Work Step by Step

$-\sqrt {36}= -\sqrt {(6)^{2}}=-(6)^{2\times\frac{1}{2}}=-(6)=-6$

Published by
Pearson

ISBN 10:
0321726391

ISBN 13:
978-0-32172-639-1

$-6$

$-\sqrt {36}= -\sqrt {(6)^{2}}=-(6)^{2\times\frac{1}{2}}=-(6)=-6$

You can help us out by revising, improving and updating this answer.

Update this answerAfter you claim an answer you’ll have **24 hours** to send in a draft. An editor
will review the submission and either publish your submission or provide feedback.